C/EBPα and GATA-2 mutations induce bilineage acute erythroid leukemia through transformation of a neomorphic neutrophil-erythroid progenitor - Di Genua, C; Valletta, S; Buono, M; Stoilova, B; Sweeney, C; Rodriguez-Meira, A; Grover, A; Meng, Y; Beveridge, R; Aboukhalil, Z; Karamitros, D; Belderbos, ME; et al. (Cell Press, 2020)
Acute erythroid leukemia (AEL) commonly involves both myeloid and erythroid lineage transformation. However, the mutations that cause AEL and the cell(s) that sustain the bilineage leukemia phenotype remain unknown. We here show that combined biallelic Cebpa and Gata2 zinc finger-1 (ZnF1) mutations cooperatively induce bilineage AEL, and that the major leukemia-initiating cell (LIC) population has a neutrophil-monocyte progenitor (NMP) phenotype. In pre-leukemic NMPs Cebpa and Gata2 mutations synergize by increasing erythroid transcription factor (TF) expression and erythroid TF chromatin access, respectively, thereby installing ectopic erythroid potential. This erythroid-permissive chromatin conformation is retained in bilineage LICs. These results demonstrate that synergistic transcriptional and epigenetic reprogramming by leukemia-initiating mutations can generate neomorphic pre-leukemic progenitors, defining the lineage identity of the resulting leukemia.